Magia, crisi e malattia: Ellenberger e de Martino - Iacarella, Andreas (Il sogno della farfalla, 2023)
The deep interest for anthropology that H. F. Ellenberger nurtured throughout his life has become object of study by historiography in recent years. This has allowed to identify some crucial aspects of his research’s method. Drawing from the brief exchange of letters that occurred between the Swiss scholar and the anthropologist E. de Martino, the aim of this essay is to offer a new interpretation of some crucial topic exposed in The discovery of the unconscious (primitive healings, “creative illness”) by bringing together the two thinkers’ ideas.